Numerical simulation study of corrosion behavior of Ni-P coating under multiple working conditions. Issue 1 (1st December 2022) - Zuo, Youxing; He, Danna; Wang, Shixin; Yu, Ziyuan
Abstract: The research on marine corrosion protection is very important in modern naval warfare. In this paper, combined with the working environment and usage requirements of underwater equipment, a 3D modeling is carried out based on a certain type of underwater equipment, and the model was divided into regions according to the difference between the base material, and the electrochemical corrosion protection was established through the finite element simulation software COMSOL Multiphysics. The simulation model was used to simulate and analyze the corrosion laws of various parts of the equipment under three different working conditions. According to the simulation results, the corrosion rate of the equipment under the protection of Ni-P chemical coating is much lower than the natural corrosion rate and the corrosion rate in seawater with a 30% concentration of Na2 SO3 corrosion inhibitor, and the Ni-P chemical coating has a good anti-corrosion effect. This paper puts forward suggestions for the follow-up improvement and development of the corrosion protection research of this type of underwater equipment and provides a reference for the research on the corrosion behavior of other metals.